Mechanical Distribution and New Bone Regeneration After Implanting 3D Printed Prostheses for Repairing Metaphyseal Bone Defects: A Finite Element Analysis and Prospective Clinical Study - Liu, Bingchuan; Li, Xingcai; Qiu, Weipeng; Liu, Zhongjun; Zhou, Fang; Zheng, Yufeng; Wen, Peng; Tian, Yun (Frontiers in Bioengineering and Biotechnology, 2022)
Critical metaphyseal bone defects caused by nonunion and osteomyelitis are intractable to repair in clinical practice owing to the rigorous demanding of structure and performance. Compared with traditional treatment methods, 3D printing of customized porous titanium alloy prostheses offer feasible and safe opportunities in repairing such bone defects. Yet, so far, no standard guidelines for optimal 3D printed prostheses design and fixation mode have been proposed to further promote prosthesis stability as well as ensure the continuous growth of new bone. In this study, we used a finite element analysis (FEA) to explore the biomechanical distribution and observed new bone regeneration in clinical practice after implanting 3D printed prostheses for repairing metaphyseal bone defects. The results reflected that different fixation modes could result in diverse prosthesis mechanical conductions. If an intramedullary (IM) nail was applied, the stress mainly conducted equally along the nail instead of bone and prosthesis structure. While the stress would transfer more to the lateral bone and prosthesis’s body when the printed wing and screws are selected to accomplish fixation. All these fixation modes could guarantee the initial and long-term stability of the implanted prosthesis, but new bone regenerated with varying degrees under special biomechanical environments. The fixation mode of IM nail was more conducive to new bone regeneration and remodeling, which conformed to the Wolff’s law. Nevertheless, when the prosthesis was fixed by screws alone, no dense new callus could be observed. This fixation mode was optional for defects extremely close to the articular surface. In conclusion, our innovative study could provide valuable references for the fixation mode selection of 3D printed prosthesis to repair metaphyseal bone defect.